The impact of social media on university students’ consumptive behavior in fashion product purchases - Rofida Putri; Sita Nurmasitah (Cendikia : Media Jurnal Ilmiah Pendidikan, 2026)
This study aims to examine the influence of social media on university students’ consumptive behavior in purchasing fashion products. A quantitative explanatory survey was conducted involving 120 active students from the Family Welfare Education Study Program, Faculty of Engineering, Universitas Negeri Semarang, selected through purposive sampling. Data were collected using a validated online questionnaire and analyzed through descriptive statistics and simple linear regression. The findings reveal that social media has a positive and significant effect on students’ consumptive behavior (r = 0.736, R² = 0.541, p < 0.001), indicating that greater exposure to fashion-related content is associated with stronger consumptive tendencies. The study concludes that social media has become a key determinant of students’ fashion purchasing behavior, highlighting the importance of strengthening digital literacy, financial literacy, and self-control to encourage more rational consumption. The novelty of this study lies in its integrated examination of social media as a digital ecosystem encompassing promotional content, influencer marketing, fashion trends, product reviews, and continuous information exposure, rather than focusing only on purchase intention or influencer credibility as in previous studies.